The Relation Between Direct Social Action and Repoliticisation: The Case of the New Case del Popolo in South Italy - Pietron, Florian (PARTECIPAZIONE E CONFLITTO, 2021)
This contribution aims to analyse the political effects of direct social action through the case of Potere al Popolo, a young radical left movement born in Italy. The strategy of this movement is based on a network of Case del Popolo where activists participate in direct social action such as free legal advice, alternative cultural activities or food distribution. Focusing our research on South Italy, this form of collective action will be analysed through the concepts of the actionalist theory. This will allow us to understand to what extent these new Case del Popolo can act as hubs for repoliticisation. The data used in this article are based on a qualitative method including interviews in the sites under investigation, a participant observation and the analysis of the communication of the political movement.